Registration of 'Alba' Barley. Issue 1 (22nd September 2014) - Graebner, Ryan C.; Cuesta-Marcos, Alfonso; Fisk, Scott; Brouwer, Brook O.; Jones, Stephen S.; Hayes, Patrick M.
Abstract : 'Alba' (Reg. No. CV‐355, PI 672535) is a winter, six‐row barley ( Hordeum vulgare L.) released by the Oregon Agricultural Experiment Station in 2012. The name Alba was chosen due to the bright and attractive appearance of the crop at maturity. In high rainfall environments, it has a notable yield advantage over check cultivars and maintains excellent test weight and kernel plumpness. These advantages are attributable in part to resistance to barley stripe rust (incited by Puccinia striiformis f. sp. hordei ) and scald (incited by Rhynchosporium commune ). The principal end‐use of Alba grain is as feed, but it could also be used for food (after pearling). Preliminary tests show that it can also be successfully malted and used in craft brewing.